Aerobic biodegradation of 2, 6-dichlorophenol in a nitrifying granular sludge reactor: System performance and microbial community evolution. (October 2020) - Wei, Dong; Li, Mingrun; Meng, Qianqian; Yan, Liangguo; Feng, Rui; Zhang, Yongfang; Fan, Dawei; Pang, Xuehui; Du, Bin; Wei, Qin
Graphical abstract: Highlights: Behavior of 2, 6-DCP co-metabolism of were evaluated in a NGS-SBR system. More protein-like substances were released from EPS under 2, 6-DCP stress. EEM implied that SMP were reduced after long-term 2, 6-DCP addition. Amaricoccus and Acidovorax were responsible for 2, 6-DCP biodegradation. Abstract: In the present study, the changes in nitrification performance, microbial products, and microbial community were evaluated in a nitrifying granular sludge (NGS) system for co-metabolic degradation of 2, 6-dichlorophenol (2, 6-DCP). After the 90-d acclimation period, the removal efficiencies of NH4 + -N and 2, 6-DCP reached 99.8 % and 99.9 %, respectively. The presence of 2, 6-DCP caused the NGS to release more protein-like substances to protect the NGS from toxic environments. The activities of ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria in the NGS were enhanced in the presence of 2, 6-DCP, and the enhancement of AOB activity improved the co-metabolism ability of NGS. The increase in nitrification capacity might have been a positive effect of 2, 6-DCP co-metabolic biodegradation. Moreover, Amaricoccus and Acidovorax were the main strains involved after long-term operation in the degradation of 2, 6-DCP in the NGS sequencing batch reactor.